The Effectiveness of Quantum Learning Methods in Group Guidance to Improve Student Motivation in Class VIII A MTS Darul Ulum 2 Widang - Freda Angga Antariksa (Buana Pendidikan, 2021)
For human life, motivation is very important, including student motivation as a driving force in the spirit of learning. The purpose of this study was to determine the effect of student motivation with the quantum learning method in group guidance to increase student learning motivation. One group pre-test design is the design used in this study on the population of 16 students of class VIII-A. The data analysis technique used by this researcher is a non-parametric analysis using the Wilcoxon test. The result of interpretation using the Wilcoxon test is known that Asymp. Sig (2-tailed) is 0.046. Because the value of 0.046 is smaller than <0.05, it can be concluded that Ho is rejected and Ha is accepted. it can be concluded that there is an effect of the quantum learning method in group guidance to increase the learning motivation of class VIII A students of MTs Darul Ulum 2 Widang